КОЛЫМСКИЕ РАССКАЗЫ В.Т. ШАЛАМОВА КАК ПАЛИМПСЕСТ - ЖАРАВИНА, ЛАРИСА (Studia Rossica Posnaniensia, 2006)
The article focuses on an analysis of Kolyma stories by V. Shalamov in the light of the palimpsest theory as a form of intertextuality. The author shows mythological, religiousphilosophical and cultural-historical levels of narration. The article highlights the role of N. Gogol’s tradition in forming literary imagery.